Formation of Histamine in Flying Fish (Hirundichthys coramandelensis) at Ambient Temperature and in Ice - P.K., Vijayan; Joseph, Jose; K., Gopakumar (Fishery Technology, 2025)
Histamine formation in flying fish (Hirundichthys coramandelensis) at ambient temperature (30Â±2"C) and in ice was studied along with other non-protein components and sensory qualities. The histamine content was within the limits on storage up to 9 h at ambient temperature, while at 11 h it was at the limit of acceptability. A positive relation was noticed between histamine content and TMAN-TVBN content as well as sensory qualities. During iced storage the histamine formation was negligible, reaching only 0.22 mg lOOg-l fish by 17 days.